(untitled) (Global Journal of Science Frontier Research, 2015)
The Traffic Light approach as a technical procedure was first developed for monitoring the status and level of risk faced by a fish population from fishery-related, environmental, and economic variables (Caddy 1999a). It has also facilitated stock management and stock recovery, in both cases where supporting data series and stock assessment skills were limited. Nonetheless, since the early 2000’s, the range of applications for this methodology have proliferated dramatically into most social and economic sectors, and after a description of the application of the traffic light procedure to fisheries, a second objective of this paper is to show some examples of the recent diffusion of this methodology to a much wider range of applications.